Radiation-induced skin reactions: oxidative damage mechanism and antioxidant protection - Liu, Chuchu; Wei, Jinlong; Wang, Xuanzhong; Zhao, Qin; Lv, Jincai; Tan, Zining; Xin, Ying; Jiang, Xin (Frontiers in Cell and Developmental Biology, 2024)
According to official statistics, cancer remains the main reason of death and over 50% of patients with cancer receive radiotherapy. However, adverse consequences after radiation exposure like radiation-induced skin reactions (RISR) have negative or even fatal impact on patients' quality of life (QoL)quality of life. In this review we summarize the mechanisms and managements of RISRs, a process that involve a variety of extracellular and intracellular signals, among which oxidative stress (OS)oxidative stress are now commonly believed to be the initial part of the occurrence of all types of RISRs. As for the management of RISRs, traditional treatments have been widely used but without satisfying outcomes while some promising therapeutic strategies related to oxidative stressOS still need further researches. In the context we discuss how oxidative stressOS leads to the happening of RISRs of different types, hoping it can shed some light on the exploration of new countermeasures.